Analisis Spasial Faktor Risiko Lingkungan pada Balita Stunting di Kecamatan Payung Sekaki Kabupaten Solok Tahun 2023 - Noeris, Zakia Rahmidini; Onasis, Aidil; Sugriarta, Evino; Wijayantono, Wijayantono; Hidayanti, Rahmi (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
Environmental risks have an influence on the incidence of stunting in toddlers caused by chronic malnutrition and repeated infections, especially in the First 1000 Days of Life (1000 HPK). One of the highest stunting contributing areas in Solok Regency is Payung Sekaki District in the Sirukam Health Center working area, there are 112 cases of stunting toddlers spread across 3 villages, namely Nagari Sirukam, Nagari Supayang and Nagari Aie Luo. The purpose of this study was to determine the spatial distribution of environmental risk factors in stunting toddlers in Payung Sekaki District, Solok Regency in 2023. The method used in this research is quantitative descriptive analysis method. The number of samples was 73 houses. Data analysis was carried out univariately and spatially using Microsoft Excel software and overlay on QGIS. This research produces information in the form of spatial distribution maps with low, medium and high classifications. With this research, it is known that Jorong Gantiang is the jorong with the highest incidence of stunting with 14 cases, Jorong Lubuak Pulai with 12 cases, and 3 jorong with moderate cases and 6 other jorong with low stunting cases. The high incidence of stunting in Payung Sekaki Sub-district is influenced by several environmental risk factors, namely the physical condition of the house, the provision of clean water, the management of waste water and feces, and having a history of recurrent infectious diseases such as diarrhea and ARI.